Partisipasi Masyarakat Terkait Pengelolaan Sampah di Kelurahan Fatululi Kota Kupang - Kamore, Kristanto; Kotan Y. Stefanus; Rafael Rape Tupen (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Waste is becoming a new problem, as there are fewer and fewer landfills and more and more waste is being produced. The lack of public awareness also exacerbates the waste problem. The purpose of this research is to find out the increase in community participation related to waste management and to find out what are the factors that hinder community participation related to waste management in Fatululi Village, Kupang City. This research is empirical juridical in nature, namely research whose data is obtained through direct tracing at the research location, in Fatululi Village, Kupang City. The type of approach used is the literature approach, Field Study Approach with qualitative descriptive analysis techniques. The results of this study show that community participation in waste management in Fatululi Village, Kupang City can be said to be low because people still litter and lack of community participation in community service activities. In the implementation of waste management in Fatululi Village, the Department of Cleanliness and Environment faces several obstacles, namely very low community participation, facilities in the form of minimal waste management facilities and infrastructure and there is still no local regulation governing sanctions for people who litter.